Word on the Idiolects Intersection: Intertextual and Metalingual Aspects (on the memoirs of Mykhailyna Kotsyubynska) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article, on the example of some lexemes and lexicalized word combinations, shows the ways how the elements of Vasyl Stus’ idiolect / individual discourse function in «The Book of Memories» by Mykhailyna Kotsyubynska and are introduced into the text via metalingual means, correlate with the meaning of statements and establish interrelations between the idiolects. The stress is made upon the intertextual nature of such signs and their important role in the conceptualization.
Keywords: idiolect; intertextuality; metalanguage; language personality; «people of the sixties» language